Mounted bass from the Philadelphia Aquarium (Philadelphia Evening Bulletin, 1927)
"This mounted red drum channel bass was a pet at the aquarium in Fairmount Park for ten years and until its death last year. It now hangs on an Aquarium wall as an exhibit. Edward Grossman (left), 1813 N. 28th st., and Bertram Lange, 2111 Montgomery av., hold the board on which the big bass, caught at Atlantic City in 1916, is mounted. The bass weighed fifty pounds on its arrival at the Aquarium and gained ten pounds in ten years. It became so tame it ate from the hands of visitors." With clipping